2004
DOI: 10.1177/1461445604044295
|View full text |Cite
|
Sign up to set email alerts
|

Repetition and Joking in Children’s Second Language Conversations: Playful Recyclings in an Immersion Classroom

Abstract: Repetition is often associated with traditional teaching drills. However, it has been documented how repetitions are exploited by learners themselves (Duff, 2000). In a study of immersion classroom conversations, it was found that playful recyclings were recurrent features of young learners’ second language repertoires. Such joking events were identified on the basis of the participants’ displayed amusement, and they often involved activity-based jokes (Lampert, 1996) and meta pragmatic play, that is, joking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 29 publications
0
51
0
3
Order By: Relevance
“…Androutsopoulos 2014). This kind of repetition is common in the learning of a second language and is discussed by Čekaitė and Aronsson (2004)) as recycling of prior participants' utterances, which is not seen as imitative in any mechanistic way. Instead this involves some kind of perspective-taking, teasing, joking or parody.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Androutsopoulos 2014). This kind of repetition is common in the learning of a second language and is discussed by Čekaitė and Aronsson (2004)) as recycling of prior participants' utterances, which is not seen as imitative in any mechanistic way. Instead this involves some kind of perspective-taking, teasing, joking or parody.…”
Section: Resultsmentioning
confidence: 99%
“…One such example is a study of joking events in L2 classrooms, by Čekaitė and Aronsson (2004), who found that playful language use was employed by intertextual play and role appropriations. The researchers argue that in instances of language play, students were temporarily freed from the monotonous business of language learning, resulting in more vivid conversation.…”
Section: Language Play In L2 Learningmentioning
confidence: 99%
“…From a social perspective, the ludic reformulations sensitize pupils with linguistic aspects, pragmatic as well as formal. Pupils advance in their linguistic consciousness and in the social rules knowledge when generating a caricature or making a joke (Cekaite & Aronson, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In those situations, the children seem to interpret the Swedish lexemes according to how they sound in Finnish. They focus on the phonological features instead of the semantics of the words (see also Cekaite & Aronsson, 2004). In later cases, the children orient to the meaning of the words (see ex.…”
Section: Child Orients To the Verbal Turnmentioning
confidence: 99%